Targeting tumor-associated acidity in cancer immunotherapy - Lacroix, Ruben; Rozeman, Elisa A.; Kreutz, Marina; Renner, Kathrin; Blank, Christian U. (Cancer Immunology, Immunotherapy, 2018)
Checkpoint inhibitors, such as cytotoxic T-lymphocyte-associated protein-4 (CTLA-4) and programmed cell death-1 (PD-1) monoclonal antibodies have changed profoundly the treatment of melanoma, renal cell carcinoma, non-small cell lung cancer, Hodgkin lymphoma, and bladder cancer. Currently, they are tested in various tumor entities as monotherapy or in combination with chemotherapies or targeted therapies. However, only a subgroup of patients benefit from checkpoint blockade (combinations). This raises the question, which all mechanisms inhibit T cell function in the tumor environment, restricting the efficacy of these immunotherapeutic approaches. Serum activity of lactate dehydrogenase, likely reflecting the glycolytic activity of the tumor cells and thus acidity within the tumor microenvironment, turned out to be one of the strongest markers predicting response to checkpoint inhibition. In this review, we discuss the impact of tumor-associated acidity on the efficacy of T cell-mediated cancer immunotherapy and possible approaches to break this barrier.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Acidity; Cancer; Checkpoint blockade; Immune therapy; Lactic acid; Metabolism